If it's not what You are looking for type in the equation solver your own equation and let us solve it.
65+11x-17=189
We move all terms to the left:
65+11x-17-(189)=0
We add all the numbers together, and all the variables
11x-141=0
We move all terms containing x to the left, all other terms to the right
11x=141
x=141/11
x=12+9/11
| v=-5 | | 9n+18=-72 | | 3²-2×3+u=(3³-3×8)(2)+u | | 5(c+4/3)+6=50 | | 3k-24=8k+32 | | 9(x-1)=5x+16 | | 2.5·t-t=3+1.5·t | | 9-2*3+u=(3³-3*8)(2)+u | | 5m-8=1.7 | | -t/2+7=-3 | | 4+5a+2a=5a+8 | | 9x+2(2-1/2)=9-2x | | 3x+2(-3+5x)=1-x | | 3x–5=-14 | | -3+10=15t-8 | | 2k-1=4-2 | | -z/3+4=5 | | -33-3n=-9(11n-7) | | 10n+20=5n-35 | | 6x=4×+20 | | 5y-15=5(y-2) | | 3-(x-9)=15 | | -6(x-3)=3 | | 80x=25+5 | | 3r-21=-37 | | 6(m+3)=5(m-2) | | 4(-3(-2n-10/2)+4n=5(n+12) | | 6(m+3)=5(m-×) | | 9x+3-7x=-15 | | 11x-56=18+9x | | -19-v=-20v | | r/4=7/5 |